Biomaterials: Nano‐spaced Gold on Glassy Carbon Substrate for Controlling Cell Behavior (Adv. Mater. Interfaces 11/2020). Issue 11 (10th June 2020) - Chauhan, Gaurav; Ángeles, Alejandro Lujambio; Gonzalez‐González, Everardo; Kulkarni, Manish M.; Cardenas‐Benitez, Braulio; Jiménez, Martín Francisco; Trujillo‐de Santiago, Grissel; Alvarez, Mario M.; Madou, Marc; Martinez‐Chapa, Sergio O.
Abstract : In article number 2000238 Gaurav Chauhan, Marc Madou, Sergio O. Martinez‐Chapa, and co‐workers present a controlled and scalable process to grow nano‐spaced gold nanoparticles on glassy carbon surface. Nanoparticle growth mechanisms inside a photocrosslinking and carbonizing SU8 matrix are detailed along with the technology to develop novel 3D carbon‐gold composites microstructures.